2019
DOI: 10.32861/bmer.59.134.141
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Dividend Payout Policy of Listed Corporations in Nigeria

Abstract: This study examines the underlying components that determine the dividend policy statement of corporations in Nigeria. The study purposively select ninety-four (94) corporations out of the universe of companies listed in the Nigerian Stock Exchange. Financial ratios were extracted and computed from published annual audited financial reports spanning 2007 to 2017. This was informed by the ex-post facto research design adopted to observe key indicators of these corporations in retrospect. The panel regression an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 0 publications
1
7
0
5
Order By: Relevance
“…The result of this study is the same with the explanation of Badu (2019); Hartono & Matusin (2020); Rizqia et al (2013); Sari (2017); Sharma & Bakshi (2019);and Wahjudi (2020). This shows that the company pay dividends to shareholders, not because of the level of profit earned but due to some considerations given by the management (Badu, 2019;Wahjudi, 2020). This considerations such as investment opportunities help to suppress dividends and increase profit earned (Rizqia et al, 2013).…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…The result of this study is the same with the explanation of Badu (2019); Hartono & Matusin (2020); Rizqia et al (2013); Sari (2017); Sharma & Bakshi (2019);and Wahjudi (2020). This shows that the company pay dividends to shareholders, not because of the level of profit earned but due to some considerations given by the management (Badu, 2019;Wahjudi, 2020). This considerations such as investment opportunities help to suppress dividends and increase profit earned (Rizqia et al, 2013).…”
Section: Discussionsupporting
confidence: 85%
“…The study of Badu (2019); Bostanci et al (2018); Patra et al (2012); and Sharma & Bakshi (2019) showed that liquidity positively affect dividend policy. According to Wahjudi (2020) showed that liquidity negatively affects dividend policy.…”
Section: Liquidity On Dividend Policymentioning
confidence: 99%
See 3 more Smart Citations